The study in cockscomb mineral composition - A. S. Deyneka; V. V. Protska; I. O. Zhuravel; O. A. Kyslychenko; V. Yu. Kuznietsova (Zaporozhye State Medical University, 2021)
Cockscomb (Сelosia cristata (L.) Kuntze) is grown in Ukraine mostly as a decorative plant. According to literature, it contains phenolic, terpenic, steroid, and nitrogen-containing compounds, showing a large range of biological activity. The aim of the work was to study qualitative composition and determination of quantitative content of mineral elements in cockscomb roots, stems, leaves, flowers, and seeds. Materials and methods. The mineral composition of cockscomb raw material was studied by atomic absorption spectroscopy. Results. In cockscomb roots, stems, leaves, flowers, and seeds 19 mineral elements were identified and determined. The bulk of mineral elements was accumulated in cockscomb leaves - 11580.54 ± 289.51 μg/100 g. In all samples of the herb potassium dominated within the limits of 1125.00 ± 28.12 μg/100 g to 7000.00 ± 175.00 μg/100 g. Prevailing microelements were iron in plant roots and seeds (210.00 ± 5.25 μg/100 g and 81.00 ± 2.02 μg/100 g respectively), aluminum in leaves and flowers (215.00 ± 2.25 μg/100 g and 44.00 ± 1.10 μg/100 g respectively), zinc in stems (5.70 ± 0.14 μg/100 g). Besides, such microelements as zinc (53.00 ± 1.33 μg/100 g) and strontium (21.20 ± 0.53 μg/100 g) were mostly accumulated in roots, manganese (27.00 ± 0.68 μg/100 g) in leaves, copper (2.00 ± 0.05 μg/100 g) in flowers. The content of heavy metals was within the limits stipulated in Ukrainian Pharmacopoeia. Conclusions. The obtained results will be used in the standardization of cockscomb raw material and in the development of medicines on the basis of this raw material.